The anthropocene biogeography of alien birds on islands: Drivers of their functional and phylogenetic diversities - Clara Marino; Lysandre Journiac; Chunlong Liu; Jonathan M. Jeschke; Céline Bellard (Ecology Letters, 2024)
A branch of island biogeography has emerged to explain alien species diversity in the light of the biogeographic and anthropogenic context, yet overlooking the functional and phylogenetic facets. Evaluating alien and native birds of 407 oceanic islands worldwide, we built structural equation models to assess the direct and indirect influence of biotic, geographic, and anthropogenic contexts on alien functional diversity (FD) and phylogenetic diversity (PD). We found that alien taxonomic richness was the main predictor of both diversities. Anthropogenic factors, including colonization pressure, associated with classic biogeographical variables also strongly influenced alien FD and PD. Specifically, habitat modification and human connectivity markedly drove alien FD, especially when controlled by taxonomic richness, whereas the human population size, gross domestic product, and native PD were crucial at explaining alien PD. Our findings suggest that humans not only shape taxonomic richness but also other facets of alien diversity in a complex way.